Selected Papers from the 9th World Congress on Industrial Process Tomography - Soleimani, Manuchehr (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Industrial process tomography (IPT) is becoming an important tool for Industry 4.0. It consists of multidimensional sensor technologies and methods that aim to provide unparalleled internal information on industrial processes used in many sectors. This book showcases a selection of papers at the forefront of the latest developments in such technologies.